Hamlet and Lameth - Brljak, Vladimir (Array, 2011)
The article identifies and examines a series of parallels between Shakespeare's Hamlet and the traditional accounts of the biblical patriarch Lamech. It is argued that these parallels – including a hitherto unacknowledged anagrammatic link between the names "Hamlet" and "Lameth", an alternative form of Lamech's name employed in various medieval and post-medieval English works – are more numerous and specific than has been previously acknowledged, with important implications for our understanding of the play.